Design and Kinematics Analysis of Wheel-leg Hybrid Robot with Four-legs - Zheng Hui; Wang Min; Wang Xinjie; Wang Caidong (Jixie chuandong)
According to the problem that the wheeled robots have poor ability to adapt terrain,and the legged robot moving speed is limited,a wheel-leg hybrid robot with four-legs is designed,which can both crawl and roll.And the robot is driven by steel wire rope with torsional spring scheme to realize switching function of working manner.In the overall design of the robot,the legs are detailed designed.The kinematic equation of standing leg is established by the D-H method,and the correctness of the kinematic equations is verified by Geometric method.The swinging leg motion space is obtained by MATLAB software.And the ability of the robot obstacle is analyzed.